ナンキョク ビボークオーセネ ト オングルカルベントウ ノ ケイソウ - 福島, 博; フクシマ, ヒロシ; FUKUSHIMA, Hiroshi (国立極地研究所, 1963)
P(論文) This is a report on the investigations of 13 algal materials given by Dr. T. TORII, reader of wintering team, 4th Japanese Antarctic Research Expedition. Dr. T. TORII collected 4 bottles of algae at Ongul Kalven Island in Lutzow-Holm Bay on July 10, 1960, 2 bottles at Hamna in the Antarctic Continent on August 27, 1960 and 7 bottles at Bybog Osane on August 9 and 27, and September 2, 1960. Ongul Kalven Island The writer could not find any diatom in 2 bottles, out of the four. In the rest, 4 kinds of diatoms were found. These were Achnanthes gainii, Charcotia australis, C. irregularis, Coscinodiscus furcatus, the number of individuals being few. Hamna in the Antarctic Continent Diatoms were not found in the materials collected from the icebergs there. Bybog Osane in the Antarctic Continent The place located on the south of the Honhorbrygga Glacier. The materials were collected from the pond. All of the 7 bottles contain diatoms, though the number is different. Amphora sp. and Navicula muticopsis f. murrayi were common but the other (Amphora sp. and Nitzschia dubia v. australis) were very few. The one bottle was Amphora sp. association and the other Navicula muticopsis f. murrani association. departmental bulletin paper